2019
DOI: 10.1038/s41598-019-42400-w
|View full text |Cite
|
Sign up to set email alerts
|

Functional conservation of EXA1 among diverse plant species for the infection by a family of plant viruses

Abstract: Since the propagation of plant viruses depends on various host susceptibility factors, deficiency in them can prevent viral infection in cultivated and model plants. Recently, we identified the susceptibility factor Essential for poteXvirus Accumulation 1 ( EXA1 ) in Arabidopsis thaliana , and revealed that EXA1-mediated resistance was effective against three potexviruses. Although EXA1 homolog genes are found in tomato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 51 publications
(67 reference statements)
0
17
2
Order By: Relevance
“…Consistent with these studies, results of our phosphoproteomic meta-analysis revealed ABA-dependent responsiveness of the phosphorylation status of host components that regulate RNA stability, turnover, maturation, and translation initiation. These included (1) factors known to be needed for potyvirus (eIFiso4G1, but not eIFiso4G2) or potexvirus infection (EXA1) ( Nicaise et al, 2007 ; Yusa et al, 2019 ); (2) regulators of the emerging antiviral pathway of RNA decay, such as those involved in mRNA decapping (i.e., VCS and VCR) and 5′-3′ mRNA decay (XRN2, XRN3, LARP1A); (3) determinants of mRNA turnover, such as UBP1C, PUM2, PUM4, and TUDOR-SN PROTEIN 2 (TSN2); and (4) components necessary for mRNA splicing, including coilin, a protein recently linked to SA signaling activation in response to virus infection ( Mäkinen et al, 2017 ; Chantarachot and Bailey-Serres, 2018 ; Li and Wang, 2019 ; Shaw et al, 2019 ; Xu et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with these studies, results of our phosphoproteomic meta-analysis revealed ABA-dependent responsiveness of the phosphorylation status of host components that regulate RNA stability, turnover, maturation, and translation initiation. These included (1) factors known to be needed for potyvirus (eIFiso4G1, but not eIFiso4G2) or potexvirus infection (EXA1) ( Nicaise et al, 2007 ; Yusa et al, 2019 ); (2) regulators of the emerging antiviral pathway of RNA decay, such as those involved in mRNA decapping (i.e., VCS and VCR) and 5′-3′ mRNA decay (XRN2, XRN3, LARP1A); (3) determinants of mRNA turnover, such as UBP1C, PUM2, PUM4, and TUDOR-SN PROTEIN 2 (TSN2); and (4) components necessary for mRNA splicing, including coilin, a protein recently linked to SA signaling activation in response to virus infection ( Mäkinen et al, 2017 ; Chantarachot and Bailey-Serres, 2018 ; Li and Wang, 2019 ; Shaw et al, 2019 ; Xu et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…EXA1 orthologs are found in a wide range of plant species, including tomato, rice, and N. benthamiana , and knockdown of EXA1 orthologs in tomato and N. benthamiana significantly reduced the accumulation of potexviruses and the related lolavirus. This restriction of viral infection is cancelled by complementation with the rice EXA1 gene, indicating that the proviral function of EXA1 is conserved among a wide range of plants (Yusa et al, 2019). However, the effect of EXA1 knockdown in N. benthamiana on virus accumulation differs depending on virus species, suggesting that EXA1 paralogs function redundantly in a virus‐specific manner.…”
Section: Resistance Genes Effective Against Plamvmentioning
confidence: 99%
“…To obtain full-length cDNA from ClYMV-JPN-2021, reverse transcription was conducted using GeneRacer oligo(dT) primer (Invitrogen, USA), which hybridizes the 3′ poly(A) tail of the potexvirus genome. PCR was performed on the cDNA using a ClYMV 1F primer designed on the 5′-end sequence determined by 5′ RACE and a KpGR3nest primer designed on the GeneRacer oligo(dT) primer ( 12 ). The amplified ClYMV-JPN-2021 genome was inserted into the pPPVOu binary vector ( 13 ) as described previously ( 12 ), and six clones were sequenced by primer walking using the primers listed in Table 1 .…”
Section: Announcementmentioning
confidence: 99%
“…PCR was performed on the cDNA using a ClYMV 1F primer designed on the 5′-end sequence determined by 5′ RACE and a KpGR3nest primer designed on the GeneRacer oligo(dT) primer ( 12 ). The amplified ClYMV-JPN-2021 genome was inserted into the pPPVOu binary vector ( 13 ) as described previously ( 12 ), and six clones were sequenced by primer walking using the primers listed in Table 1 . Using ATGC v4.3.5 software (Genetyx, Japan), all sequence reads from the six clones were trimmed and assembled into a single contig with 100% identity in each of the overlapping regions.…”
Section: Announcementmentioning
confidence: 99%